Polarization processes in vitreous oxide semiconductors of the bi//2o//3-v//2o//5-cao system; The Soviet journal of glass physics and chemistry; Vol. 12, № 1 - Kalygina V. M.; Gaman V. I.; Kosintsev V. I. Victor Ivanovich; Modebadze O. E. (1986, 1986)
This report discusses the temperature and frequency dependences of the conductivity and dielectric constant of vitreous oxide semiconductors (VOS) with the aim of refining the transport mechanism of the charge carriers in them. The dc ( sigma // minus ) and ac ( sigma approximately) conductivity and dielectric constant ( epsilon prime ) were measured for specimens of a capacitor type with sputtered Nichrome electrodes. The dielectric constant and the conductivity in the region of (2 multiplied by (times) 10**2-2 multiplied by (times) 10**4) Hz were determined by a bridge method using an E8-2. At frequencies of (1. 5-3) multiplied by (times) 10**9 Hz the measurements of epsilon prime were carried out using a resonator method. It is found that in view of the ac transport mechanism of charge carriers in vitreous oxide semiconductors, it is necessary to take into account both the hopping and tunnel transitions of the SRP (Small Radius Polarons). The polarization process of the Debye type observed in VOS in the low